Current banana smallholder farmers' farming practices and knowledge on plant-parasitic nematodes associated with banana (Musa spp.) in Rusitu Valley, Zimbabwe - Chitamba, James; Manjeru, Pepukai; Mudada, Nhamo; Chinheya, Cleopas Chenai (Academic Journals, 2020)
Plant-parasitic nematodes are economically important pests of banana (Musa spp.) and compromise its productivity. Controlling nematode populations and good agronomic practices are pre-requisites for a good yield. A survey of farmers in the Rusitu Valley, Zimbabwe, was conducted to assess their current banana production practices and knowledge of plant-parasitic nematodes associated with banana. Respondents were selected using systematic sampling from three wards. Most farmers (61.9%) grew bananas as a monoculture, and 38.1% intercrop banana with other crops. All the farmers neither rotated banana with other crops nor practiced pest and disease control measures, and only 11.4% apply a fertiliser to their banana crops. Most (82.9%) farmers in Rusitu Valley had little or no knowledge of plant-parasitic nematodes that damage bananas. Sound extension programme in Rusitu Valley should educate farmers on the importance of managing plant-parasitic nematodes and using better banana crop production practices.